2009
DOI: 10.1155/2009/914501
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterizations of Bare CdS Nanocrystals Using Chemical Precipitation Method for Photoluminescence Application

Abstract: Bare cadmium sulfide (CdS) nanocrystals were successfully synthesized by the thermolysis of a single-source organometallic precursor, cadmium chloride hemipentahydrate (CdCl 2 · 2.5H 2 O) with thiourea in ethanol. The microstructure of the CdS samples was characterized using XRD, TEM, and Raman spectroscopy. The XRD's results showed that there was a transformation from cubic to hexagonal crystalline phase when higher mass of CdCl 2 · 2.5H 2 O was used. Further experimental with different Cd 2+ source showed io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
(50 reference statements)
3
24
0
Order By: Relevance
“…We confirmed the presence of the CdS layer by XPS (X-Ray Photoelectron Spectroscopy) measurements. We observe the S2p line at 162.0 eV, which is attributed to the CdS bond [30][31][32]. Based on the intensities of the S2p, Cd3d and Te3d lines, and considering their sensitivity factors, we estimate the thickness of this CdS layer as two or three atomic layers.…”
Section: Synthesis and Methodsmentioning
confidence: 94%
“…We confirmed the presence of the CdS layer by XPS (X-Ray Photoelectron Spectroscopy) measurements. We observe the S2p line at 162.0 eV, which is attributed to the CdS bond [30][31][32]. Based on the intensities of the S2p, Cd3d and Te3d lines, and considering their sensitivity factors, we estimate the thickness of this CdS layer as two or three atomic layers.…”
Section: Synthesis and Methodsmentioning
confidence: 94%
“…In Figure 1 (top), the experimental and the theoretical (vertical lines) X-ray Diffractogram are shown. By analyzing XRD it can be observed that the CdS/Cd(OH) 2 QDs present cubic crystalline structure, which corresponds to the more stable crystalline form for CdS [23]. Contrast phase image obtained for the same times, 3 minutes and 7 days, are presented in Figure 5 left and right, respectively.…”
Section: -Resultsmentioning
confidence: 94%
“…Along with similarly synthesized colloidal cadmium selenide quantum dots (Q-CdSe) of 1.7 eV bandgap, both Q-CdS and Q-CdSe, with their corresponding absorption onsets of $520 and 720 nm, respectively, offer the opportunity for a range of investigations and optical technology development throughout the visible spectrum. Moreover, since Q-CdS exhibit the characteristics of multiple colors and brightness, comparable to that of fluorescent dyes and semiconductor light emitting diodes, several research groups have worked to explore their properties [11][12][13][14][15]. However, more research will be needed to convert Q-CdS from a ''promising electronic material'' to the realm of device applications.…”
Section: Discussionmentioning
confidence: 99%